CONTROLE QUÃMICO DA PODRIDÃƒO BRANCA (Sclerotium cepivorum Berk.) DO ALHO (Allium sativum L.) - Sinigaglia, Celso; Ramos, Reinaldo da Silva; Issa, Eduardo; Chiba, Soyako (REVISTA DE AGRICULTURA, 2015)
CONTROLE QUÃMICO DA PODRIDÃƒO BRANCA (Sclerotium cepivorum Berk.) DO ALHO (Allium sativum L.)